Pengenalan Pembukuan Sederhana untuk Entrepreneur Keluarga Mandiri di Kader Posyandu Kp. Rawa Lele, Ciputat-Tangerang Selatan - Haryoso, Gunung Subagyo Anom; Aditya Riky Nugroho; Irwan Setiawan (Universitas Pamulang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the growth and development of the Indonesian economy in general and the South Tangerang region in particular. To manage these businesses, MSMEs still need knowledge of simple bookkeeping and taxation. Recognizing this, one of the roles of universities is to contribute to providing knowledge about bookkeeping and taxes for MSMEs. This community service aims to provide insight into the preparation of financial reports and taxation for MSMEs. The service was carried out at the Posyandu Cadre Forum in Rawa Lele Village, Jombang Village, Ciputat District, South Tangerang. The target of this service was the mothers of the Posyandu cadres in Rawa Lele Village, Jombang Village, Ciputat District, South Tangerang. Problems that occurred in the partners were resolved in several stages of activities, namely preparation, implementation, and evaluation. Preparation was carried out by conducting a preliminary survey related to the problems faced by partners. Implementation was carried out through training and mentoring using the material presentation method followed by discussion and questions and answers. Evaluation of this stage was carried out by collecting and summarizing data from each activity stage. The results of the community service activities showed a level of success with the suitability of the material topics with the information needed by the mothers of the Posyandu cadres in Rawa Lele Village in facing future challenges. After receiving counseling, the mothers of the Posyandu cadres in Rawa Lele Village will be in the community and have the opportunity to develop themselves in the field of entrepreneurship at the MSME level. This community service program has enthusiastically provided participants with responses to the PKM material and increased their knowledge and awareness of the importance of simple bookkeeping for MSMEs and their tax applications. Keywords: Financial Reports, Taxation, Mentoring, Socialization, MSMEs.